Analysis of Hand Tractor Needs in Paddy Field Cultivation in Bangbang Village, Tembuku District, Bangli - Darma, I Gede Agus Arya; Aviantara, I Gusti Ngurah Apriadi; Tika, I Wayan (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Agricultural cultivation requires optimal management of hand tractor needs. The number of hand tractors required depends on the area of agricultural land. This study aimed to determine the need for hand tractors and plan the optimal number as a recommendation. Quantitative analysis was conducted through survey methods to obtain primary data, namely field measurements. The results showed that the speed of the hand tractor was 0.686 m/s. The effective land capacity was 0.0366 ha/hour, while the theoretical land capacity was 0.066 ha/hour. The hand tractor had a field efficiency of 55.45%. Based on these results, Bangbang Village requires 15 units of hand tractors for agricultural processing.